Do’s and Don’t s of Partnering with Industry to Educate Software Engineering Students: Recommendations Based on a Teaching Experience - Goelzer, Natalya Marjana; Possamai, Pedro Portella; Marczak, Sabrina (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.11193, 2025)
This experience report describes a software development training program for undergraduate students, resulting from a longstanding collaboration between the Pontifical Catholic University of Rio Grande do Sul (PUCRS) and a renowned multinational in the technology industry, one of the largest retailers in the global IT market. The program aims to prepare students for professional software development before they formally join industry teams. Established over 25 years ago, the program currently trains around 60 students per year and has followed its current structure since 2016. This paper characterizes the university-industry partnership model and presents an overview of the program’s four main phases: (1) participant selection, (2) technical training, (3) hands-on practice, and (4) industry internship. The first three phases take place within the university. The discussion highlights key challenges and successes identified throughout each stage, and analyzes how early exposure to industry-aligned practices helps bridge the gap between academic learning and real-world professional demands. The experience report also synthesizes lessons learned through a summary of Do’s and Don’t s for each phase, offering practical recommendations for similar initiatives.